Student satisfaction in clinical area subjects during the COVID-19 pandemic in a medical school - Diaz-Lazo, Anibal; Alvarez-Risco, Aldo; Córdova Rosales, Carlo; Cori Rosales, Sandra; Ruiz-Aquino, Mely; Del-Aguila-Arcentales, Shyla; Davies, Neal M.; Mejia, Christian R.; Yáñez, Jaime A. (Frontiers in Education, 2024)
Coronavirus SARS-CoV-2 had an impact on health, and education, among other subjects. It caused changes in teaching medicine. The study's objective was to determine student satisfaction in the subjects of the clinical area in a medical school during the coronavirus SARS-CoV-2 pandemic. The current study has an observational, descriptive, and cross-sectional design. The sample consisted of 119 students. Inclusion criteria included being a student enrolled in the 2021-2 semester, between the VI and XII semesters in a medical school. It was found that the median age was 21 years; 68 (57.1%) were male. Overall student satisfaction was 67.1%. High student satisfaction was found in the dimension development of professional skills (84.9%), achievement of student expectations (69.7%) and virtual assistance (67.2%), at a medium level of student satisfaction. Flexibility in learning (64.7%), the use of infrastructure and facilities (61.7%), and the use of educational resources (61.3%) were reported. The students were generally satisfied with the dynamic communication of the teachers, especially concerning promoting student participation (79%) Introduction The appearance of the type 2 coronavirus, which causes severe acute respiratory syndrome (SARS-CoV-2), has had a negative impact on health (